Distribution and Coexistence of Myoclonus and Dystonia as Clinical Predictors of SGCE Mutation Status: A Pilot Study - Zutt, Rodi; Dijk, Joke M.; Peall, Kathryn J.; Speelman, Hans; Dreissen, Yasmine E. M.; Contarino, Maria Fiorella; Tijssen, Marina A. J. (Frontiers in Neurology, 2016)
Introduction Myoclonus–dystonia (M–D) is a young onset movement disorder typically involving myoclonus and dystonia of the upper body. A proportion of the cases are caused by mutations to the autosomal dominantly inherited, maternally imprinted, epsilon-sarcoglycan gene (SGCE). Despite several sets of diagnostic criteria, identification of patients most likely to have an SGCE mutation remains difficult. Methods Forty consecutive patients meeting pre-existing diagnostic clinical criteria for M–D underwent a standardized clinical examination (20 SGCE mutation positive and 20 negative). Each video was reviewed and systematically scored by two assessors blinded to mutation status. In addition, the presence and coexistence of myoclonus and dystonia was recorded in four body regions (neck, arms, legs, and trunk) at rest and with action. Results Thirty-nine patients were included in the study (one case was excluded owing to insufficient video footage). Based on previously proposed diagnostic criteria, patients were subdivided into 24 “definite,” 5 “probable,” and 10 “possible” M–D. Motor symptom severity was higher in the SGCE mutation-negative group. Myoclonus and dystonia were most commonly observed in the neck and upper limbs of both groups. Truncal dystonia with action was significantly seen more in the mutation-negative group (p < 0.05). Coexistence of myoclonus and dystonia in the same body part with action was more commonly seen in the mutation-negative cohort (p < 0.05). Conclusion Truncal action dystonia and coexistence of myoclonus and dystonia in the same body part with action might suggest the presence of an alternative mutation in patients with M–D.